EVALUATION OF INSECTICIDES AGAINST SUCKING INSECT PESTS INFESTING BT COTTON BG- II - T. M. BHARPODA; N. B. PATEL; R. K. THUMAR; N. A. BHATT; L. V. GHETIYA; H. C. PATEL; P. K. BORAD (The Bioscan, 2014)
Nine synthetic insecticides were evaluated against sucking insect pests viz., leaf hopper (Amrasca biguttula biguttula Ishida), whitefly (Bemisia tabaci Gennadius), thrips (Thrips tabaci Lindemann) and aphid (Aphis gossypii Glover) in cotton variety RCH-2 Bt (BG-II) during three consecutive years i.e. 2009-10, 2010-11 and 2012-13. Among the different insecticides, imidacloprid 17.8 SL @ 0.008% (7.50 aphid and 1.47 whitefly/ leaf), thiamethoxam 25 WG @ 0.0125% (1.22 leaf hopper/ leaf) and diafenthiuron 50 WP @ 0.05% (1.43 thrips/ leaf) found more effective and safer to the natural enemies viz., Chrysoperla carnea (adult), spiders and coccinellids (grubs and adult). Highest seed cotton yield (30.81 q/ha) was harvested from crop treated with imidacloprid followed by clothianidin (27.34 q/ha), difenthiuron (26.93 q/ha), thiamethoxam (26.01 q/ha) and acetamiprid (25.68 q/ha). The highest Insecticidal Cost Benefit Ratio (1: 16.54) was registered in imidacloprid followed by acetamiprid (11.06), acephate (10.38), thiamethoxam (7.05) and difenthiuron (6.13).